Case report: Prenatal diagnosis of fetal intracranial hemorrhage due to compound mutations in the JAM3 gene - Xu, Min; Jin, Pengzhen; Huang, Yingzhi; Qian, Yeqing; Lin, Miaochun; Zuo, Juan; Zhu, Jin; Li, Zhaohui; Dong, Minyue (Frontiers in Genetics, 2022)
Intracranial hemorrhage is a common complication in preterm infants but occasionally occurs in fetuses. Disruptions of the genes, such as the COL4A1 and COL4A2 genes, are common genetic causes identified in fetal intracranial hemorrhage; however, the disruptions of the JAM3 gene are rarely reported. In the current investigation, fetal intracranial hemorrhage and dilated lateral ventricles were observed in three consecutive siblings in a pedigree. The pregnancies were terminated, and whole-exome sequencing, followed by Sanger sequencing, was performed on the affected fetuses. Pre-implantation genetic testing for monogenic diseases was performed to avoid the recurrence. The compound heterozygous variants of c.712 + 2T > A and c.813C > G p.Tyr271* in the JAM3 gene (NM_032801.4) were identified in the proband and its affected brother, which were predicted to be pathogenic. The variant of c.813C > G p.Tyr271* but not c.712 + 2T > A was identified in the fourth fetus, implying a good prognosis. Our findings expanded the spectrum of the pathogenic mutations in the JAM3 gene and revealed an important application of fetal whole-exome sequencing in idiopathic fetal intracranial hemorrhage.